High protein intake causes gene-length-dependent transcriptional decline, shortens lifespan and accelerates ageing in progeroid DNA repair-deficient mice - Ivar van Galen; Maria B. Birkisdóttir; Rutger A. Ozinga; Renata M. C. Brandt; Sander Barnhoorn; Sandra Imholz; Conny T. van Oostrom; Ricfrid W. G. N. van der Marel; Kimberly Smit; Yvonne M. A. Rijksen; Erwin Reiling; Harry van Steeg; et al. (npj Metabolic Health and Disease)
Abstract Dietary composition can significantly influence health and lifespan, however, robust knowledge on which food components, at what concentration exert which long-term health effects is still incomplete. Here, we explored the effects of dietary protein intake on Ercc1 Δ/− DNA-repair-deficient mice, which are an excellent model for accelerated ageing and are hyperresponsive to the anti-ageing effect of dietary restriction. Restricting dietary protein by 50% extended lifespan in male mice, but not in females. Restricting protein levels beyond 80% improved various neurological health parameters, while a further reduction to 95% affected appetite and became distinctly detrimental. Conversely, a near doubling of protein intake and isocaloric compensatory lowering with carbohydrates significantly shortened lifespan in both sexes. Gene expression analysis of liver from mice on a high-protein, low-carbohydrate diet to those on high-carbohydrate, low-protein revealed increased expression of oxidative phosphorylation, enrichment of processes associated with tissue injury, inflammation, and gene-length-dependent transcriptional decline (GLTD), recently shown to reflect DNA damage accumulation causing transcription stress, and cellular ageing. Finally, GLTD was also identified by reanalysis of publicly available data of wild-type mice, rats and humans on high-protein diets, suggesting that increased dietary protein enhances GLTD and accelerates systemic ageing. Together, our findings have implications for nutritional guidelines for progeroid DNA-repair-deficient human syndromes, warrant the use of excessive protein intake for sustaining health, and suggests GLTD as a sensitive read-out of overall health and predictor of biological ageing.